A standard method to synthesize Ag, Ag/Ge, Ag/TiO2, SnO2, and Ag/SnO2 nanomaterials using the HVPG technique - Muflikhun, Muhammad Akhsin (Animo Repository, 2019)
Nanotechnology is growing rapidly in the past few decades with the applications in several fields such as medicine, environment, energy, electronics, automotive, and aerospace. There are many methods used by researchers to synthesize nanomaterial. In this paper, Horizontal Vapor Phase Growth (HVPG) technique was successfully used to synthesize various nanomaterial and nanocomposite materials such as Ag, Ag/Ge, Ag/TiO2, SnO2, and Ag/SnO2. HVPG technique used a one-pot step to synthesize nanomaterials with 100 % purity of the results, affordable cost, and environmentally friendly. The method has two variables; growth temperature and curing time. Changing the variables create different shapes of nanomaterials. It also reported that the technique could be used to synthesize various nanomaterials consists of single or multi-material. This detailed method demonstrates the capability of the HVPG technique to synthesize nanomaterials, not only to grow the single shape of nanomaterials but also allow other nanomaterial shapes to grow in different parameter conditions. • HVPG technique successfully used to synthesize various nanomaterials. • Only 2 parameters used; curing time and growth temperature. • Purity result (100 %) with no pollutant. © 2019 The Author(s)